CORAK ‘ILMĪ TAFSIR AL-MISBAH - Firdarini Firdarini; Moh. Anwar Syarifuddin (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
This study aims to reveal portray Quranic verses interpreted using the scientific style of interpretation by M. Quraish Shihab in his Tafsir al-Misbah. Its existence has been revealed by Moh. Anwar Syarifuddin and Jauhar Azizy in their 2014 report on "Islamic Relations and Science and Technology in the Indonesian Tafsir Literature", but using only the Madaniyya verses of the five first chapters of the Qur’an. The present writer examined there surahs: al-Nahl (the Bees), al-Naml (the Ants) and al-Ankabut (the Spider), all of which are animal names but categorized as Makkiyah instead. Research question of this piece is what is proven to be the scientific style of interpretation within the interpretation of those three surahs in Tafsir al-Misbāḥ? This is qualitative research along with the descriptive analytical method. The findings strengthen the previous findings which also show a very high level of appreciation indicated by the writer of al-Misbah in interpreting 33 Quranic verses within their scientific color of interpretation, in which it is a lot higher than the previous findings on the Madaniyya verses.